PENINGKATAN PANGSA PASAR UMKM BATIK MELALUI OPTIMALISASI PEMASARAN DIGITAL BERBASIS WEB - Ulil Hartono; Anang Kistyanto; Fandi Fatoni; Yuyun Isbanah; Ika Diyah Candra Arifah (Universitas Mataram, 2022)
The business continuity of MSME entrepreneurs is affected by the COVID-19 pandemic, especially those engaged in batik fashion, where fashion shows or exhibitions are cancelled. To support batik entrepreneurs, product and technology innovations that adapt to market conditions are needed. In order to increase sales of batik fashion in the pandemic era through digitalization, an appropriate marketing strategy is needed to increase technological literacy that has a positive impact on increasing market share.This community service activity aims to analyze and implement strategies to increase the market share of batik MSMEs through optimizing web-based digital marketing. This type of community service is field research with a qualitative descriptive approach. The method of data collection was carried out by survey and observation methods. The implementation of the training uses tutorial and lecture techniques. The implementation of community service is carried out in 4 stages, namely the identification of batik UMKM partner problems, formulation of partner problem solutions, providing e-commerce training in the form of e-commerce web design training and content creation, and evaluation and assistance in the form of partner understanding and satisfaction surveys. SMEs in Kampung Batik Lemahputro, Sidoarjo have implemented several forms of web-based marketing applications into their businesses, but their level of use is limited to basic marketing applications such as e-mail and static websites. However, MSMEs already have a moderate understanding of the benefits of web-based marketing and more than 50 percent of SMEs indicated that they are aware that web-based marketing can improve overall performance and profitability.